Electron microscopy characterization of Pd-Ce interaction on α-Al2O3 support - Moreno, Mario Sergio Jesus (2008)
The reforming reaction of CH4 with CO2 has motivated numerous studies in search of active and selective catalysts. The endothermic character of this reaction requires a high reaction temperature to obtain acceptable conversion levels. The high operating temperature produces the sintering of metallic particles, and deactivation of the catalyst by the formation and accumulation of carbonaceous deposits. The use of CeOx in a Pd/a-Al2O3 catalyst reduces the formation of carbonaceous deposits. Understanding the role of Ce in the reforming reaction demands a direct visualization of the Ce distribution and a local study of the initial Pd oxidation state